If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(8x + (5x + -30)) = 12 Reorder the terms: 7x + -1(8x + (-30 + 5x)) = 12 Remove parenthesis around (-30 + 5x) 7x + -1(8x + -30 + 5x) = 12 Reorder the terms: 7x + -1(-30 + 8x + 5x) = 12 Combine like terms: 8x + 5x = 13x 7x + -1(-30 + 13x) = 12 7x + (-30 * -1 + 13x * -1) = 12 7x + (30 + -13x) = 12 Reorder the terms: 30 + 7x + -13x = 12 Combine like terms: 7x + -13x = -6x 30 + -6x = 12 Solving 30 + -6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -6x = 12 + -30 Combine like terms: 30 + -30 = 0 0 + -6x = 12 + -30 -6x = 12 + -30 Combine like terms: 12 + -30 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| 3b+3s=21 | | 6v+10=64 | | x^2+2x+1=65 | | 3(cx+1)=6x+4 | | 6x+5+4x=66+4x | | -4=5t+6 | | (4x^2)+4=9 | | 5(5x-2)=153+2(20-2x) | | x+8=4.24 | | -6+8r=-6+8r | | S+26=8 | | x-6=-27 | | 0.2x+7.2=10 | | -3(2w-6)+4(-1-5w)=0 | | w*7*w*3*w=131 | | 40x^4-60x^3+20x=0 | | 5x-2=-3x+6 | | (3x+y)6= | | 5(y-2)-2=2(v+1)-5 | | 5B+3V=27.50 | | (x^2)-x-10=0 | | 4x^2+4=148 | | 5x-12-23x=6(-3x-2) | | 46-46x=(7x+3)(x-1) | | p=12x-5x | | 6-4x=4(1-x) | | 35-(2x-14)=40-(x+2) | | (2x^2)-x-(3)=0 | | 5x^2=23x+10 | | 40-7n=2(-5n+6)-n | | 8w/6+8=w-2 | | 12(4x-6)=8x+5(8x-6) |